Pivotal Study of a Novel Motor-Driven Endoscopic Ablation System. (11th February 2021) - Schmidt, Boris; Petru, Jan; Chun, K.R. Julian; Sediva, Lucie; Bordignon, Stefano; Chen, Shaojie; Neuzil, Petr
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The HeartLight endoscopic ablation system has proven similar efficacy as radiofrequency guided pulmonary vein (PV) isolation in prospective randomized studies though longer procedure times were reported. Recently, the option of a new ablation mode (RAPID) was added, during which the laser arc generator is swept around the PV antrum by an integrated motor drive at a predefined speed for continuous ablation. We sought to determine the performance of the new endoscopic ablation system (X3). Methods: The study was prospective, 2-center, and historically controlled (comparison to pivotal HeartLight study). The primary end point was ablation time (time from insertion of the X3 catheter to the end of the last 30-minute wait period). Transtelephonic monitoring was performed from 90 days to 12 months after ablation. Results: A total of 60 patients were enrolled at 2 centers. Except one, all PVs were treated with RAPID mode. Acute PV isolation was achieved in 225/228 of these PVs (98.7%). The ablation time was significantly shorter with X3 than in the HeartLight study (77.3±25.8 versus 173.8±46.6 min; P <0.0001). Procedure time and fluoroscopy time were also significantly shorter (103.7±32.3 versus 236.0±52.8 min; P <0.0001; 6.9±3.5 versus 35.6±18.2; P <0.0001). PV isolation after the first circular lesion was achieved in 91.6% of PVs (206/225). Two strokes and one late pericardial effusion were noted in the treatment group that were not deemed device related. The 6-month and 12-month atrial fibrillation–free rates for X3 compare favorably with the rates reported for HeartLight, 89.5% versus 75.0% and 71.9% versus 61.1%, respectively. Conclusions: The novel X3 generation endoscopic ablation system allows for rapid PV isolation by continuous lesion deployment. This was associated with a significant reduction in ablation and procedure times while maintaining the safety and chronic effectiveness in comparison to historical controls. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03470636.